Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)A=\(x^5-\dfrac{1}{2}x+7x^3-2x+\dfrac{1}{5}x^3+3x^4-x^5+\dfrac{2}{5}x^4+15\)
=\(=\dfrac{-5}{2}x+\dfrac{36}{5}x^3+\dfrac{17}{5}x^4+15\)
b)B=\(3x^2-10+\dfrac{2}{5}x^3+7x-x^2+8+7x^2\)
\(=9x^2+\dfrac{2}{5}x^3+7x+2\)
c)C=\(\dfrac{1}{7}x-2x^4+5x+6\)
* Trả lời:
\(\left(1\right)\) \(-3\left(1-2x\right)-4\left(1+3x\right)=-5x+5\)
\(\Leftrightarrow-3+6x-4-12x=-5x+5\)
\(\Leftrightarrow6x-12x+5x=3+4+5\)
\(\Leftrightarrow x=12\)
\(\left(2\right)\) \(3\left(2x-5\right)-6\left(1-4x\right)=-3x+7\)
\(\Leftrightarrow6x-15-6+24x=-3x+7\)
\(\Leftrightarrow6x+24x+3x=15+6+7\)
\(\Leftrightarrow33x=28\)
\(\Leftrightarrow x=\dfrac{28}{33}\)
\(\left(3\right)\) \(\left(1-3x\right)-2\left(3x-6\right)=-4x-5\)
\(\Leftrightarrow1-3x-6x+12=-4x-5\)
\(\Leftrightarrow-3x-6x+4x=-1-12-5\)
\(\Leftrightarrow-5x=-18\)
\(\Leftrightarrow x=\dfrac{18}{5}\)
\(\left(4\right)\) \(x\left(4x-3\right)-2x\left(2x-1\right)=5x-7\)
\(\Leftrightarrow4x^2-3x-4x^2+2x=5x-7\)
\(\Leftrightarrow-x-5x=-7\)
\(\Leftrightarrow-6x=-7\)
\(\Leftrightarrow x=\dfrac{7}{6}\)
\(\left(5\right)\) \(3x\left(2x-1\right)-6x\left(x+2\right)=-3x+4\)
\(\Leftrightarrow6x^2-3x-6x^2-12x=-3x+4\)
\(\Leftrightarrow-15x+3x=4\)
\(\Leftrightarrow-12x=4\)
\(\Leftrightarrow x=-\dfrac{1}{3}\)
Mình chỉ giải câu a) thôi nhé. 4/5-1/3.x=3/2 1/3.x=4/5-3/2 1/3.x=-7/10 x=-7/10:1/3 x=-21/10
x^5-3*x^2-(7*x^4-9*x^3+x^2-1/4*x+5*x^4-x^5+x^2-2*x^3+3*x^2-1/4)=0
a: P(x)=x^4-2x^4-5x^3-7x^2+2x-1
=-x^4-5x^3-7x^2+2x-1
Q(x)=3x^4-2x^4+5x^3+6x^2-2x+5
=x^4+5x^3+6x^2-2x+5
a) 2x.3/5 - 5x = 3/2 - 7x
6x/5 - 5x = 3/2 - 7x
-19x/5 = 3/2 - 7x
-19x = 15/2 - 35x
-19x + 35x = 15/2
16x = 15/2
x = 15/2 : 16
x = 15/32
b) (x - 1/5)2 = 4/25
(x - 1/5)2 = (+-2/5)2
x - 1/5 = +-2/5
x - 1/5 = 2/5 hoặc x - 1/5 = -2/5
x = 2/5 + 1/5 x = -2/5 + 1/5
x = 3/5 x = -1/5